2020
DOI: 10.3390/ijms21031057
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the Undifferentiated State in Myogenic Progenitor Cells by TGFβ Signaling is Smad Independent and Requires MEK Activation

Abstract: Transforming growth factor β (TGFβ) is a pluripotent cytokine and regulates a myriad of biological processes. It has been established that TGFβ potently inhibits skeletal muscle differentiation; however, the molecular mechanism is not clearly defined. Previously, we reported that inhibition of the TGFβ canonical pathway by an inhibitory Smad, Smad7, does not reverse this effect on differentiation, suggesting that activation of receptor Smads (R-Smads) by TGFβ is not responsible for repression of myogenesis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…One of the interesting nding of the present study was that M2 polarized macrophages increased the expression of OT and OTR in enteric neurons, which might be mediated by TGF-β. TGF-β mainly regulated downstream cell responses through Smad and non-Smad signaling pathways [31,42]. Our experiments con rmed that TGF-β activated Smad2/3 and promoted the expression of OT and OTR.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…One of the interesting nding of the present study was that M2 polarized macrophages increased the expression of OT and OTR in enteric neurons, which might be mediated by TGF-β. TGF-β mainly regulated downstream cell responses through Smad and non-Smad signaling pathways [31,42]. Our experiments con rmed that TGF-β activated Smad2/3 and promoted the expression of OT and OTR.…”
Section: Discussionsupporting
confidence: 62%
“…3.4. Smad2/3 pathway was involved in the upregulation of OT/OTR expression following TGF-β TGF-β induces cellular response by binding transmembrane receptors [30] and phosphorylation of Smad2/3 (receptor regulated Smads: R-Smads) [31]. In this study, we found that the expression of p-Smad2 and p-Smad3 were up-regulated following TGF-β treatment for 24 h, and pretreatment of SIS3CHL (Smad3 inhibitor, 5µM) blocked this change (Fig.…”
Section: In Ammatory Cytokines Downregulated Expression Of Ot/otr Proteins In Enteric Neurons Via Stat3 or Nf-κb Pathwaymentioning
confidence: 99%
“…Similarly, Miller et al found that dynamic of the TGF-β signaling is dictated by receptor trafficking via the ESCRT machinery, especially via the HD-PTP factor [73]. A recent study identified a non-canonic activation of TGF-β receptor that inhibits the differentiation process via the upregulation of the MEK/ERK pathway, a phenotype that could be rescued by addition of U0126 MEK/ERK inhibitor [78]. Collectively, these data suggest that other potential membrane receptors of different classes that we did not explore could in absence of Hrs participate to the inhibitory effect of Hrs depletion on muscle differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…TGF-β induces a cellular response by binding transmembrane receptors [ 32 ] and phosphorylating Smad2/3 (receptor regulated Smads: R-Smads) [ 33 ]. In this study, we found that p-Smad2 and p-Smad3 expression were upregulated following TGF-β treatment for 24 h, and pretreatment with SIS3CHL (Smad3 inhibitor, 5 μM) blocked this change (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the interesting findings of the present study is that M2-polarized macrophages increase the expression of OT and OTR in enteric neurons, which might be mediated by TGF-β. TGF-β mainly regulates downstream cell responses through Smad and non-Smad signalling pathways [ 33 , 46 ]. Our experiments confirmed that TGF-β activates Smad2/3 and promotes the expression of OT and OTR.…”
Section: Discussionmentioning
confidence: 99%